The Role of Organizational Behavior in Supporting Marketing Strategies at Zahra Baju Bodo Business in Soppeng Regency - Andi Rahma Nur Alam; Asni Asni; Umar Umar; Nurhaya Ilmi; Puja Armelia; Nurhardianti Nurhardianti (GENTARA: management and accounting research, 2026)
This study aims to examine the role of organizational behavior in supporting marketing strategies in local businesses in Soppeng Regency, particularly at Zahra Baju Bodo. In an increasingly competitive business environment, business owners are required to implement effective marketing strategies to attract consumers and improve customer satisfaction. However, the success of marketing strategies is not only determined by planning but is also influenced by organizational behavior such as communication, teamwork, and leadership. This study uses a literature review method by analyzing several scientific journals, including research by Puji Rahmah, which shows that marketing strategies have an effect on customer satisfaction. The results indicate that amid the increasing competition in the Baju Bodo business, Zahra Baju Bodo is still able to attract consumers through appropriate marketing strategies supported by good organizational behavior